Adsorptive Removal of Rhodamine B Using Novel Adsorbent-Based Surfactant-Modified Alpha Alumina Nanoparticles - Thi Hai Yen Doan; Thi Phuong Minh Chu; Thi Diu Dinh; Thi Hang Nguyen; Thi Cam Tu Vo; Nhat Minh Nguyen; Bao Huy Nguyen; The An Nguyen; Tien Duc Pham (Journal of Analytical Methods in Chemistry)
The objective of the present study is to investigate removal of cationic dye, rhodamine B (RhB), in water environment using a high-performance absorbent based on metal oxide nanomaterials toward green chemistry. The adsorption of sodium dodecyl sulfate (SDS) onto synthesized alpha alumina (α-Al2O3) material (M0) at different ionic strengths under low pH was studied to fabricate a new adsorbent as SDS-modified α-Al2O3 material (M1). The RhB removal using M1 was much higher than M0 under the same experimental conditions. The optimal conditions for RhB removal using M1 were found to be contact time 30 min, pH 4, and adsorbent dosage 5 mg/mL. The maximum RhB removal using M1 achieved 100%, and adsorption amount reached 52.0 mg/g. Adsorption isotherms of RhB onto M1 were well fitted by the two-step adsorption model. The electrostatic attraction between positive RhB molecules and negatively charged M1 surface controlled the adsorption that was evaluated by the surface charge change with zeta potential and adsorption isotherms. Very high RhB removal of greater than 98% after four regenerations of M1 and the maximum removal for all actual textile wastewater samples demonstrate that SDS-modified nano α-Al2O3 is a high-performance and reusable material for RhB removal from wastewater.